The Paradox of Meritocracy: Re-examining Equity, Social Mobility, and the Role of Elite Schools in Singapore's Education System - Nurul Huda Mohamed; Alvin Tan (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2025)
This research aims to analyze the fundamental transformation in Singapore's meritocratic system, shifting from a "narrow" academic-based model to a broader "inclusive meritocracy." The study is critical now as Singapore faces a social divide where early meritocratic success has evolved into a mechanism for reinforcing social stratification. Through a comprehensive review of Forward Singapore policies, the implementation of Full Subject-Based Banding (FSBB), and 2026 social mobility data, this study explores how Singapore's educational structure responds to the challenges of entrenched privilege. The methodology employed is a descriptive-qualitative policy analysis utilizing secondary data from reports by the Ministry of Finance (MOF) and the Ministry of Education (MOE) spanning 2021-2026. Research findings indicate that while structural reforms such as the elimination of streaming and the overhaul of the Gifted Education Programme (GEP) have successfully reduced academic stigma, significant challenges persist in the form of an "educational arms race" and "hothousing" practices by upper-class families. Data from 2026 indicates a decrease in the Gini coefficient to 0.359 after taxes and transfers; however, this figure primarily reflects fiscal interventions rather than true educational mobility, as intergenerational mobility shows signs of moderation. The study concludes that strengthening equity requires an approach that goes beyond school infrastructure, focusing on the redistribution of social and cultural capital. The government should take the urgent practical step of severing the direct link between academic merit and extreme market compensation to restore the dignity of all forms of work.